Analisis Pengaruh Profitabilitas, Likuiditas, Leverage, Dan Tax Avoidance Terhadap Pengungkapan Islamic Social Reporting (ISR) ( Studi Kasus Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index 70 (JII70) Tahun 2018 - 2022 ) - Zahra Amri; Ingra Sovita (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of profitability, liquidity, leverage, and tax avoidance on the disclosure of Islamic Social Reporting (ISR) in companies listed on the Islamic Index 70 (JII70) in 2018-2022). This type of research uses quantitative research and the data used is secondary data. This research sampling technique used purposive sample technique and obtained 140 samples consisting of 28 companies listed on the Jakarta Islamic Index 70 (JII70) in 2018-2022. The data analysis technique of this study used multiple linear analysis techniques with the help of the SPSS version 21 program. The results of this study indicate that partially profitability has a positive and insignificant effect on the disclosure of Islamic Social Reporting (ISR). Liquidity has a positive and insignificant effect on the disclosure of Islamic Social Reporting (ISR). Leverage has a positive and significant effect on the disclosure of Islamic Social Reporting (ISR) and tax avoidance has a positive and significant effect on the disclosure of Islamic Social Reporting (ISR). Simultaneously, all variables have a positive and significant effect on the disclosure of Islamic Social Reporting (ISR).